Immune-Related Genes of Megalurothrips usitatus (Bagrall) Against Beauveria brongniartii and Akanthomyces attenuatus Identified Using RNA Sequencing - Chen, Yueyin; Yang, Bo; Li, Zhaoyang; Yue, Yang; Tian, Qingheng; Chen, Weiyi; Ali, Shaukat; Wu, Jianhui (Frontiers in Physiology, 2021)
Megalurothrips usitatus (Bagrall) is an important pest of legumes worldwide, causing great economic loss every year. Beauveria brongniartii and Akanthomyces attenuatus have shown considerable pathogenicity against M. usitatus in our previous studies. The medial lethal concentration (LC50) and the sublethal lethal concentration (LC25) of B. brongniartii isolate SB010 against M. usitatus were 8.38 × 105 and 1.73 × 105 conidia mL−1, respectively, whereas those of A. attenuatus isolate SCAUDCL-53 against M. usitatus were 4.37 × 105 and 2.97 × 104 conidia mL−1, respectively. This study reports the transcriptome-based explanation of the stress responses of M. usitatus following the application of B. brongniartii and A. attenuatus. The analysis of the transcriptomic data revealed the expression of 254, 207, 195, and 234 immunity-related unigenes by M. usitatus in response to B. brongniartii LC50 (SB1), B. brongniartii LC25 (SB2), A. attenuatus LC50 (V1), and A. attenuatus LC25 (V2), respectively. The biological function and metabolic pathway analyses showed that these unigenes were mainly related to pattern recognition receptors, information transduction factors, and reaction factors, such as scavenger receptor, cytochrome b5, cuticle protein, lysozyme, and serine protease.